2020
DOI: 10.1038/s41438-020-0265-9
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and interspecific diversity analyses in the genus Eremurus in Iran using genotyping-by-sequencing reveal geographic population structure

Abstract: Eremurus species, better known as 'Foxtail Lily' or 'Desert Candle', are important worldwide in landscaping and the cutflower industry. One of the centers of highest diversity of the genus Eremurus is Iran, which has seven species. However, little is known about the genetic diversity within the genus Eremurus. With the advent of genotyping-bysequencing (GBS), it is possible to develop and employ single nucleotide polymorphism (SNP) markers in a costefficient manner in any species, regardless of its ploidy leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The fleshy roots of E. spectabilis Clade II [24] were collected from its natural habitat (Figure 1), i.e., Golestan National Park, Golestan province, Iran (UTM zone: 37 • 32 49.8 (37.5472 • ) N and 56 • 23 22.4 (56.3896 • ) E), during the start of the dormant season. The Foxtail lily has tuberous roots.…”
Section: Plant Materialsmentioning
confidence: 99%
“…The fleshy roots of E. spectabilis Clade II [24] were collected from its natural habitat (Figure 1), i.e., Golestan National Park, Golestan province, Iran (UTM zone: 37 • 32 49.8 (37.5472 • ) N and 56 • 23 22.4 (56.3896 • ) E), during the start of the dormant season. The Foxtail lily has tuberous roots.…”
Section: Plant Materialsmentioning
confidence: 99%
“…This study aimed to evaluate the impact of using different Gleditsia rootstocks on the scion growth and development of Gleditsia plants, including (i) graft compatibility and the extent of compatibility among different Gleditsia species, (ii) the effects of different rootstocks on the morphology, physiology, and hormone levels of Gleditsia plants, and (iii) the differences between homograft and heterograft combinations. GBS is a cost-effective method for developing SNP markers without the need to consider the genome size, ploidy level, or the presence of background genomic sequences; this method allows for the genotyping of all markers derived from a population [40,41]. ISSR markers have the advantages of having rich polymorphism, a low cost, simple operation, high stability, and co-dominance, and they have been widely used in studies of plant germplasm selection, interspecific differentiation, and population diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Bagged inflorescences do not produce seeds in all the selected populations.Also The present study revealed that Eremurus persicus is diploid with chromosome number of 2n = 2x = 14. The karyotype analysis revealed that various species of the genus Eremurus have 2n chromosome counts of 14 and 28 (Hadizadeh et al, 2020). Somatic chromosome analysis of eight species of Aloe (Asphodelaceae) showed diploid chromosome number of 2n = 14 (Sánchez-Get al 2018).…”
Section: Reproductive Outputmentioning
confidence: 99%